GENDER PERFORMATIVITY IN CHAINANI’S THE SCHOOL FOR GOOD AND EVIL NOVEL - Fitriani, Alfisyahrin; Sunggingwati, Dyah; Nasrullah, Nasrullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
It is started since the canonical story of Adam and Eve, individuals are labeled right after their birth as, “it’s a girl” or “it’s a boy”. This binary system of women (girl) and men (boy) continues to have a default setting that women should align with her gender that is feminine, while men should be masculine. The presumption of the default alignments also intersects to the expectation of individual’s sexuality, that is, heterosexual. The situation then dichotomizes people’s normality. This process is called social construction of gender which was asserted by Judith Butler. This research analyzed gender construction in The School for Good and Evil novel by Chainani using Judit Butler’s Gender Performativity theory. There were two discussions taken in the research. First is the identification of social construction in the novel. Second is the identification of how the two main female characters perform their gender despite the social construction of gender inscribed to them. The research used qualitative method. The researcher used a close reading process to do the data collection technique. The result of this research reveals that the social construction of gender in the novel were surrounded all aspects of human life. The society constructed body features, appearance, roles, traits, sexuality, and punishment based on individuals’ gender category. It is also found that the two main female characters were gender fluid that at certain stages they were conforming to the construction but also negating the construction.